Real-Time PET Imaging for Range Verification of Helium Radiotherapy - Ozoemelam, Ikechi; van der Graaf, Emiel; van Goethem, Marc-Jan; Kapusta, Maciej; Zhang, Nan; Brandenburg, Sytze; Dendooven, Peter (Frontiers in Physics, 2020)
Real-time range verification of particle beams is important for optimal exploitation of the tissue-sparing advantages of particle therapy. Positron Emission Tomography (PET) of the beam-induced positron emitters such as 15O (T1/2 = 122 s) and 11C (T1/2 = 1223 s) has been used for monitoring of therapy in both clinical and preclinical studies. However, the half-lives of these nuclides preclude prompt feedback, i.e., on a sub-second timescale, on dose delivery. The in vivo verification technique relying on the in-beam PET imaging of very short-lived positron emitters such as 12N (T1/2 = 11 ms), recently proposed and investigated in feasibility experiments with a proton beam, provides millimeter precision in range measurement a few tens of milliseconds after the start of an irradiation. With the increasing interest in helium therapy, it becomes relevant to study the feasibility of prompt feedback using PET also for helium beams. A recent study has demonstrated the production of very short-lived nuclides (T1/2 = 10 ms attributed to 12N and/or 13O) during irradiation of water and graphite with helium ions. This work is aimed at investigating the range verification potential of imaging these very short-lived nuclides. PMMA targets were irradiated with a 90 AMeV 4He pencil beam consisting of a series of pulses of 10 ms beam-on and 90 ms beam-off. Two modules of a modified Siemens Biograph mCT PET scanner (21 × 21 cm2), installed 25 cm apart, were used to image the beam-induced PET activity during the beam-off periods. For the irradiation of PMMA, we identify the very short-lived activity earlier observed to be 12N (T1/2 = 11.0 ms). The range precision determined from the 12N activity profile that is measured after just one beam pulse was found to be 9.0 and 4.1 mm (1σ) with 1.3 × 1074He ions per pulse and 6.6 × 1074He ions per pulse, respectively. When considering 4.0 × 1074He ions, which is about the intensity of the most intense distal layer spot in a helium therapy plan, a range verification precision in PMMA of 5.7 mm (1σ) can be realized. The range precision scales approximately with the inverse square root of the number of 4He ions, i.e., the relative statistical accuracy of the number of coincidence events. Thus, when summing data over about 10 distal layer spots, this study shows good prospects for obtaining 1.8 mm (1σ) precision in range verification, within 50 ms after the start of a helium irradiation by in-beam PET imaging (scanner 29% solid angle) of 12N.